Cinnamaldehyde and hesperetin attenuate TNBS‐induced ulcerative colitis in rats through modulation of the JAk2/STAT3/SOCS3 pathway. Issue 5 (31st January 2021) - Elhennawy, Mayada G.; Abdelaleem, Eglal A.; Zaki, Amal A.; Mohamed, Wafaa R.
Abstract: Ulcerative colitis is an autoimmune inflammatory disorder with a negative impact on the life quality of patients. Cinnamaldehyde and hesperetin were chosen due to their antioxidants and anti‐inflammatory effects. This study explored the protective effects of cinnamaldehyde (40 and 90 mg/kg, po) and hesperetin (50 and 100 mg/kg, po) on 2, 4, 6‐trinitrobenzene sulfonic acid (TNBS)‐induced ulcerative colitis in rats. Cinnamaldehyde and hesperetin significantly improved macroscopic and histopathological examinations with a significant reduction in myeloperoxidase and intracellular adhesion molecule‐1 expression. They significantly reduced colon oxidative stress by a significant elevation in both reduced glutathione content and superoxide dismutase activity with a significant reduction of NO content. Furthermore, cinnamaldehyde and hesperetin alleviated the inflammatory injury by a significant reduction in interleukin‐6 along with suppression of nuclear factor‐κB, receptor for advanced glycation end products, and tumor necrosis factor‐α expression. Moreover, cinnamaldehyde and hesperetin significantly decreased p‐JAK2 and p‐STAT3 while significantly increased suppressors of cytokine signaling 3 (SOCS3) protein expression. In conclusion,  cinnamaldehyde and hesperetin counteracted TNBS‐induced ulcerative colitis through antioxidant, anti‐inflammatory properties as well as modulation of the JAk2/STAT3/SOCS3 pathway.